Assessing food insecurity among households : the case of Northern Perak region - Aspalila, Nur Asilah (2018)
Food security is everyone’s obligation as it involving household, national and global levels. Studies have shown that food insecurity has become a common issue that exists among low‐income households. This study aims to assess the household food insecurity status and to explore the factors that affect the household food insecurity status in Northern Perak region. A sample of 200 respondents was collected through face to face interview and direct personal administration. The instrument used to assess food insecurity is the US Household Food Security Schedule Module (US HFSSM). A structured questionnaire was designed to collect the information on demographic profile and household food insecurity status. Respondents was randomly selected by using simple random sampling technique which among the households who having income within below RM 4000 (B40) in Kerian District. The data was analyzed using descriptive analysis and binary logistic regression. Results of the survey shows that 29% of the households were food secure, while 71% experienced some kind of food insecurity. The results of study revealed that age, occupation and school-going children are important factors determining the household food insecurity status. Thus, the government should implement a programme that focuses more on younger headed household who do not have a stable financial status.